Principal's Strategy in Forming Students' Religious Character (Case Study at SD Muhammadiyah 1 Sedati, Sidoarjo) - Furqon Furqon; Nurdyansyah Nurdyansyah (International Consortium of Education and Culture Research Studies, 2020)
This study aims to explain in depth the principal's strategy in forming the religious character of students: a case study in Muhammadiyah 1 Primary School, Sedati, Sidoarjo. This research is a descriptive qualitative research. Data sources were taken from the principal, teachers, employees, students, parents of students and the general public. Data collection tools include interviews, observations, and documentation. From the results of the study illustrate that the Religious Character Building of Students in Muhammadiyah 1 Sedati Elementary School, Sidoarjo includes: (a) Al Qur'an Reading and Writing Program (BTQ) (b) Tahfidh Al Quran Learning Program (c) Implementation of Dhuhur and Asr Prayer (d) ) Customizing Smile Greetings and Shaking Hands (e) Learning ISMUBA curriculum (f) Commemoration of Islamic Holidays (PHBI) (2) The principal's strategy in building the religious character of students is manifested in religious cultured school programs in Muhammadiyah Elementary School 1 Sedati, Sidoarjo.